2019
DOI: 10.1016/j.esxm.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction Among Greek Women With Multiple Sclerosis: Correlations With Organic and Psychological Factors

Abstract: Introduction Multiple Sclerosis (MS) is a degenerative neurological disease that usually occurs between the ages of 20 and 50 years. Sexuality issues are important factors that affect the quality of life of patients. Aim To determine and evaluate the prevalence of female sexual dysfunction (FSD) in Greek women with MS and correlate it with organic and psychological factors. Methods 248 consecutive women with MS, aged over 18 who admitted to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…This finding was consistent with a previously reported correlation between depression and SD in MS (Fragala et al, 2014, Kisic-Tepavcevic et al, 2015. In addition, our study showed that anxiety disorders were common in NMOSD patients, with a prevalence of 52%, similar to that previously reported in MS (Konstantinidis et al, 2019;Shi et al, 2016). A positive correlation between anxiety and SD was described in MS patients (Fragala et al, 2014), and our study shows a similar relationship in NMOSD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was consistent with a previously reported correlation between depression and SD in MS (Fragala et al, 2014, Kisic-Tepavcevic et al, 2015. In addition, our study showed that anxiety disorders were common in NMOSD patients, with a prevalence of 52%, similar to that previously reported in MS (Konstantinidis et al, 2019;Shi et al, 2016). A positive correlation between anxiety and SD was described in MS patients (Fragala et al, 2014), and our study shows a similar relationship in NMOSD.…”
Section: Discussionsupporting
confidence: 93%
“…Among patients with MS, SD affects 40%-80% of women and 50%-90% of men (Kisic-Tepavcevic et al, 2015;Schmidt et al, 2005). Moreover, multiple studies reported that age, disability, depression, fatigue and lower urinary tract dysfunction (LUTD) are independent risk factors for the deterioration of sexual function (Fragala et al, 2014, Fragala et al, 2015, Kisic-Tepavcevic, Pekmezovic, 2015, Konstantinidis et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Physical disability of MS patients which is shown with EDSS, had negative correlation with FSFI. In a previous study, Konstantinidis at al, reported significant negative correlations between FSFI and its subscales except for desire and satisfaction (25). Alehashemi et al, and Ghajarzadeh et al reported significant negative correlation between EDSS and FSFI which confirms our findings as well as Gumus ans Gava (23,24,26,27).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, a negative and significant correlation was found between the EDSS score and the total scores of FSFI and its subscales, except for desire and pain, and studies by Alehashemi (2019) and Ghajarzadeh (2014) showed a significant negative relationship between the EDSS scores and the total FSFI scores (P = 0.032, r = 0.35 and P = 0.001, r = 0.44). Koranian (2017) also found an inverse and significant relationship between the EDSS level and the total FSFI score and its subscale scores, except for pain (P = 0.001, r = 0.61), and Konstantinidis (2019) also found an inverse and significant relationship between the EDSS level and the FSFI subscale scores, except for arousal and satisfaction [41]. Celik (2013) showed a direct and significant relationship between the EDSS score and secondary (P = 0.001, r = 0.34) and tertiary (P = 0.032, r = 0.35) SD.…”
Section: Discussionmentioning
confidence: 96%